FEA of disc L2-L3 spine segment on age-related clinical problems - Foo, Hee Suan. (2008)
This project models the disc body segment L2 and L3 to study the effect of osteoporosis and disc degeneration that effect the state of stress in the disc body. To account for stiffness effect due to posterior element, the Young’s modulus (E) was increased at the posterior region.